2020
DOI: 10.51386/25815946/ijsms-v3i6p110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Servant Leadership and Work Motivation on Organizational Citizenship Behavior: Evidence from Indonesian Generation Y Employees

Abstract: The purpose of this study is to find an effort to increase organizational citizenship behavior of Generation Y employeesthrough the identification of the influence of servant leadership and work motivation. This research wasconducted on Generation Y employeesare governmental officers aged 23 -43 years at Bogor Regency. The research sample was 86 persons of generation Y from 3 agencies and 11 offices at Bogor Regency. This research uses a quantitative approach and is completed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Research has found that the quality of the relationship between leaders and employees is very important for OCB. Servant leadership and organizational citizenship behavior have a very strong influence, servant leadership does not only function as a leader, but also serves employees (Wahyu et al, 2020). Therefore, the following hypothesis is proposed: H3: There is a positive influence of servant leadership on organizational citizenship behaviour.…”
Section: Servant Leadership and Organizational Citizenship Behaviormentioning
confidence: 99%
“…Research has found that the quality of the relationship between leaders and employees is very important for OCB. Servant leadership and organizational citizenship behavior have a very strong influence, servant leadership does not only function as a leader, but also serves employees (Wahyu et al, 2020). Therefore, the following hypothesis is proposed: H3: There is a positive influence of servant leadership on organizational citizenship behaviour.…”
Section: Servant Leadership and Organizational Citizenship Behaviormentioning
confidence: 99%